How the Quantitative Easing Affect the Spillover Effects between the Metal Market and United States Dollar Index? - Su, Jung-Bin (Journal of Reviews on Global Economics, 2016)
This study explores both return and volatility spillover effects, the co-integration relation and the correlative relationship between the metal market in London metal exchange and United States exchange rate market, and the risk premium and leverage effect in each of these two markets for the periods before and during quantitative easing (QE). Empirical results show that, as the QE is executed the risk premium in US exchange rate market will disappear; and the speed and direction of the adjustment back to equilibrium respectively becomes greater and is reversed for the co-integration relation in metal market. Regarding these two markets only the return spillover effect is affected, and the degree of negative correlative relationship becomes more obvious as the QE is executed.